Familial isolated hypoparathyroidism type 2: a case report with review of literature - Mandal, Satyajit; Chatterjee, Kaushani; Kapat, Aritra (International Journal of Contemporary Pediatrics, 2023)
Familial isolated hypoparathyroidism (FIH) is a rare group of genetic disorder associated with dysregulation of parathyroid hormonal axis characterized by refractory hypocalcaemia. Herein we report a 1 month 4 days old baby born out of consanguineous marriage presented with respiratory distress with single episode of convulsion, cause pointing towards hypocalcaemia. The hypocalcaemia symptoms were refractory despite repeated calcium gluconate. Laboratory parameters yielded evidence of hypoparathyroidism which was further strengthened by neuroimaging and skeletal imaging. The hypoparathyroidism was treated by oral calcitriol and calcium supplementation along with institution of phosphate binder. Whole genome exome sequencing revealed a novel nonsense mutation of glial cell missing transcription factor 2 (GCM2) gene variant c.109C>T (p.Gin37Ter) establishing the diagnosis as FIH type 2. The calcium and phosphate normalized in further follow up. The new found locus and the novel variation of GCM2 gene adds another feather to the ever-evolving genetic conundrum of the disease.